Electromyographic analysis of the vertebral extensor muscles during the Biering-Sorensen Test - Ligia Moreira de Santana; Paulo Roberto Carvalho do Nascimento; Thais de Sousa Lima; Ana Carolina Tocilo Lopes; Amanda Costa Araujo; Fábio Mícolis de Azevedo; Rúben de Faria Negrão Filho (Universidade Estadual Paulista (UNESP), 2014)
The purpose of the study was to analyze the electromyographic signal of the multifidus, longissimus thoracis and the lumbar iliocostalis muscles during the Biering-Sorensen test in subjects without lower back pain. Twenty volunteers performed the test on three separate occasions. An analysis of variance detected a difference between the three test times (p = 0.0026). For the frequency domain, it was observed that there were differences between the multifidus and the lumbar erectors muscles; longissimus and iliocostalis muscles. However, in the time domain analysis, no difference was observed. As the values of the slope coefficients of median frequencies were higher for the multifidus muscle, compared to the longissimus and lumbar iliocostalis muscles, this may indicate a higher tendency toward muscle fatigue. Therefore, considering the applied methodology, the study of electromyographic signals in the frequency domain should be considered as an instrument to assess fatigue of the spinal extensor muscles in clinical situations.